Atypical Presentation of Giant Mandibular Aneurysmal Bone Cyst with Cemento-Ossifying Fibroma Mimicking Sarcoma - Haneen Al-Maghrabi; Serge Verne; Bassam Al-Maghrabi; Osamah Almutawa; Jaudah Al-Maghrabi (Case Reports in Otolaryngology)
Aneurysmal bone cysts (ABCs) are an uncommon osteolytic intraosseous bone lesions. ABCs commonly involve metaphysis of long bones and are rarely diagnosed in craniofacial bones. The World Health Organization (WHO) designates ABCs as benign, but locally destructive, rapidly growing masses. ABC can be clinically misdiagnosed as a malignant tumor. In this article, we present a case of a 12-year-old female patient who presented to a maxillofascial outpatient clinic complaining of huge jaw swelling over the past 3 months, which was clinically suggestive of sarcoma. Few reported cases in the English literature describe ABC presented with huge rapidly growing mass causing destructive bony lesion that was clinically mimic sarcoma, which initiates this case report. We also discuss the most important pathologic differential diagnosis of tumors with malignant behavior and review the literature.